Continued innovation beyond COVID-19 crisis: toward mitigating the challenges in the tourism and hospitality industry - Ramachandran, Sridar; Ugokwe, Chizoba Kingsley; Latiff, Khairunnisak; Ibrahim, Mohd Romzee (Emerald, 2024)
Purpose: This paper aims to provide insights into service innovation (SI) during the COVID-19 crisis and its potential impact on tourism development in the medium-to-long term. The pandemic had a devastating effect on the industry, requiring immediate mitigation. It is yet to fully establish the impact of SI in the face of the COVID-19 volatility, uncertainty, complexity and ambiguity (VUCA). This study discusses the potential link between SI and COVID-19 crisis mitigation and offers recommendations for tourism recovery. Design/methodology/approach: This paper synthesizes empirical evidence on post-crisis tourism SI using a theory-based general literature review approach. Findings: COVID-19 crisis spun various forms of SI, which emerged as a conventional solution to crisis prevention, encompassing the management of crisis-time competitiveness, revenue deficits and risk perception. However, resistance to innovative services is linked to situational conditions. Research limitations/implications: COVID-19 is an unprecedented crisis. Therefore, this study serves as a primer for further inquiry into SI. For instance, areas such as governance in tourism innovation and consumers' inclination toward innovation-driven services are underexplored. Practical implications: SI acts as a situational facilitator, but its characteristics can impede or facilitate adoption. Moreover, the irrelevance of innovations in some environments is evidenced. Thus, practitioners must adopt a responsive learning approach in SI adoption. To mitigate the COVID-19 impacts, reconfiguration in SI, recovery marketing strategy, knowledge gap and governance will be critical interventions. Originality/value: This paper is one of the first comprehensive discussions on the potential role of SI in mitigating the impact of COVID-19 on the THI. © 2024, Sridar Ramachandran, Chizoba Kingsley Ugokwe, Khairunnisak Latiff and Mohd Romzee Ibrahim.